Karakteristik Penderita Penyakit Jantung Koroner Yang Di Rawat Inap Di RSUD dr.La Palaloi Maros Periode Januari 2022 – Desember 2023 - Ganoko, Marwan Ahmad; Saleh, Muhammad Asy’min; Amiruddin, Tedy (Barongko: Jurnal Ilmu Kesehatan, 2024)
Coronary Heart Disease is a disease of the heart and blood vessels caused by narrowing of the coronary arteries. Narrowing of blood vessels occurs due to the process of atherosclerosis due to the gradual accumulation of cholesterol and connective tissue on the walls of blood vessels. There are several risk factors related to the occurrence of coronary heart disease. These risk factors are divided into modifiable risk factors and non-modifiable risk factors. The purpose of the study was to determine the characteristics of patients with coronary heart disease based on (1) History of hypertension (2) Smoking habits (3) Age Group and (4) Gender. This study was conducted on 66 patients with coronary heart disease who were hospitalized at dr. La Palaloi Maros Hospital for the period of January 2022 – December 2023. This study uses an observational descriptive method using secondary data in the form of medical records of patients with coronary heart disease who are hospitalized at dr. La Palaloi Maros Hospital. Data analysis is processed using SPSS software. The results of this study show the distribution of coronary heart disease patients who were hospitalized at dr. La Palaloi Maros Hospital for the period January 2022 to December 2023, namely: (1) The most history of hypertension was 51 patients (77.3%), (2) The most smoking history was 36 patients (54.6%), (3) The most in the risk age group was 55 patients (83.3%), (4) More in men 46 patients (69.7%) than in women 20 patients (30.3%), The conclusion of the study is that the most people with coronary heart disease have a history of hypertension, a history of smoking habits. at-risk age group, and male.